Formulation of a Multifunctional Rose Water-Based Anti-Pollution Sunscreen and Makeup Setting Mist - Raz Nur Natasha Abdul Razak,; Angzzas Sari Mohd Kassim, (Progress in Engineering Application and Technology, 2026)
Urban environments expose skin to multiple stressors, including ultraviolet (UV) radiation and airborne pollutants, which accelerate oxidative damage, inflammation, and premature skin ageing while compromising the skin barrier. Although daily photoprotection is essential, many existing sunscreen products lack multifunctionality and fail to adequately address pollution-induced skin stress or meet consumer demand for lightweight, skin-compatible formulations. This study aimed to develop and evaluate a rose water–based anti-pollution sunscreen and makeup setting mist incorporating botanical antioxidants from Rosa damascena petals and Camellia sinensis leaves. Bioactive compounds were extracted using ultrasound-assisted aqueous extraction with Moringa oleifera coagulant and ultrasound-assisted hydroethanolic extraction. Antioxidant and anti-inflammatory activities were assessed using DPPH radical scavenging and bovine serum albumin (BSA) protein denaturation assays. Selected extracts were incorporated into sprayable mineral-based sunscreen mist formulations containing zinc oxide, optimised using Design of Experiments (DoE), and evaluated for sun protection efficacy using the Mansur spectrophotometric method. Ultrasound-assisted hydroethanol extraction produced clearer and more homogeneous extracts with superior bioactivity, attributed to enhanced recovery of polyphenolic compounds. The extracts exhibited significant antioxidant and anti-inflammatory potential, with DPPH inhibition of up to 72.21% for Rosa damascena and 78.29% for Camellia sinensis, and BSA protein denaturation inhibition reaching 66.38% and 78.94%, respectively. DoE optimisation demonstrated that physicochemical stability and uniform dispersion of mineral UV filters were critical for sun protection efficacy, with formulations R9 (≈37 SPF) and R8 (≈31 SPF) showing the best overall performance. Overall, the findings demonstrate that rose water combined with botanical antioxidants can be effectively formulated into a multifunctional facial mist providing UV protection, mitigation of pollution-related oxidative stress, and cosmetic setting performance, supporting its potential as an innovative and consumer-aligned cosmeceutical solution for urban skin protection.